Outcomes of nonsurgical endodontic treatment in teeth with large periapical lesion (Annals of Medical Research, 2021)
Aim: Present study aimed to evaluate the long-term clinical and radiographical outcomes of non-surgical root canal therapy using calcium hydroxide in anterior teeth with large periapical lesions.Material and Methods: Clinical and radiographical records of 57 mandibular and 32 maxillary anterior teeth of 74 patients were included in the study. A total of 89 anterior teeth with large periapical lesions ranging in size from 6 to 20 mm were treated endodontically with calcium hydroxide as the intracanal medicament. Teeth were evaluated in two parts as lesion diameters between 6-10 mm and 11-20 mm. All cases were followed up for 24 months and assessed in three categories as complete healing, incomplete healing or no healing (failure).Results: Complete healing was observed in 74 (83.1%), incomplete healing in 7 (7.9%) and failure in 8 (9%) teeth in all cases at the end of 24-month assessment. There was no positive correlation between the outcome of the therapy and the size of the periapical lesions (p>0.05). Conclusion: Obtained results suggested that non-surgical endodontic treatment was greatly successful in the treatment of teeth with large periapical lesions and it should be considered before surgical procedure.
Keywords: Calcium hydroxide; non-surgical root canal treatment; periapical healing; periapical lesion.